Molecular Cloning and Expression Analysis of 5-hydroxytryptamine Receptor 7 in Ant Polyrhachis vicina Roger (Hymenoptera: Formicidae). Issue 2 (28th February 2019) - Yang, Sen; Xi, Gengsi; Wang, Guirong
Abstract: Serotonin (5-hydroxytryptamine [5-HT]) is a monoamine neurotransmitter that plays an important role in regulating a variety of physiological and behavioral activities. In this study, the 5-HT 7 receptor gene was cloned from the ant Polyrhachis vicina Roger (1863). The complete Pv5-HT 7 receptor cDNA is 3054 bp, including a 5′-untranslated region (UTR) of 790 bp, a 3′-UTR of 752 bp and an open reading frame of 1512 bp encoding polypeptide of 503 amino acids. Hydrophobic analysis suggests that seven trans-membrane domains are the major sequence characteristic of the Pv5-HT 7 receptor. In addition, the Pv5-HT 7 receptor has three potential N-glycosylation sites, a palmitoylation site, three protein kinase A phosphorylation sites, and four protein kinase C phosphorylation sites. Phylogenetic analysis revealed that the deduced Pv5-HT 7 receptor sequence shared a high homology with 5-HT7 receptor sequences of other species, such as a 78% similarity with the Am5-HT 7 receptor ( Apis mellifera ). Real-time quantitative PCR (qRT-PCR) results showed that the expression level of the Pv5-HT7 receptor was low in the eggs and 1th-4th larval stages, but it was increased in the pupae stage and reached its peak in the adult workers. Western blot results showed that the highest protein expression was in the male body, head, and thorax. These results suggest that the Pv5-HT7 receptor may have specific functions in regulating the development of P. vicina, especially in adult formation and caste differentiation, feeding and caring behaviors of workers in the nest, and in the development of motor organs and mating behaviors in males.